2023
DOI: 10.3390/foods12122385
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Milk and Plant Proteins to Develop Novel Food Systems: What Are the Limits?

Abstract: In the context of a diet transition from animal protein to plant protein, both for sustainable and healthy scopes, innovative plant-based foods are being developing. A combination with milk proteins has been proposed as a strategy to overcome the scarce functional and sensorial properties of plant proteins. Based on this mixture were designed several colloidal systems such as suspensions, gels, emulsions, and foams which can be found in many food products. This review aims to give profound scientific insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…The viscosity of milk was contributed by the presence of casein, myelin, and fat globules [54]. Furthermore, the bonds between protein and fat affected viscosity; changes in casein milk with the same hydrophilic properties as other protein types caused increased viscosity [55]. Fermentation of lactose produces lactic acid, which plays a role in milk protein to produce a unique gel-like texture and odor in yogurt [56].…”
Section: Yogurt Sensorial Analysismentioning
confidence: 99%
“…The viscosity of milk was contributed by the presence of casein, myelin, and fat globules [54]. Furthermore, the bonds between protein and fat affected viscosity; changes in casein milk with the same hydrophilic properties as other protein types caused increased viscosity [55]. Fermentation of lactose produces lactic acid, which plays a role in milk protein to produce a unique gel-like texture and odor in yogurt [56].…”
Section: Yogurt Sensorial Analysismentioning
confidence: 99%
“…Based on these observations, piston-type extrusion may work better than a screw-type conveyance, as the capillary rheology experiments discussed earlier suggest that the material can flow out of an orifice die when put under pressure by a piston. Among the three polysaccharides, the fibers formed from the composites containing carrageenan exhibited the best shape retention [44]. Manual handling of the fibers indicated that their firmness increased with increasing polysaccharide concentration.…”
Section: Fiber Formation Using Extrusionmentioning
confidence: 99%
“…Some foods, such as dairy desserts and jellies, are made by gelation. The gelation of proteins involves two main processes, including protein denaturation/unfolding and then aggregation into a self-supporting structure with a 3-dimensional network [1,3,5]. The gel structure is a suitable medium for encapsulation by protecting sensitive bioactive compounds or nutraceuticals from degradation during food processing and through harsh conditions within the gastrointestinal tract [1,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…The gel structure is a suitable medium for encapsulation by protecting sensitive bioactive compounds or nutraceuticals from degradation during food processing and through harsh conditions within the gastrointestinal tract [1,4,6]. In this view, several attempts have been made to produce protein gels of different matrices that serve different purposes in the food industry [2,3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%